Drivers of information disclosure on health information exchange platforms: insights from an exploratory empirical study. (14th August 2015) - Yaraghi, Niam; Sharman, Raj; Gopal, Ram; Singh, Ranjit; Ramesh, R
Abstract: Objective The objective of this research is to empirically explore the drivers of patients' consent to sharing of their medical records on health information exchange (HIE) platforms. Materials and Methods The authors analyze a dataset consisting of consent choices of 20 076 patients in Western New York. A logistic regression is applied to empirically investigate the effects of patients' age, gender, complexity of medical conditions, and the role of primary care physicians on patients' willingness to disclose medical information on HIE platforms. Results The likelihood of providing consent increases by age (odds ratio (OR) = 1.055; P < .0001). Female patients are more likely to provide consent (OR = 1.460; P = .0003). As the number of different physicians involved in the care of the patient increases, the odds of providing consent slightly increases (OR = 1.024; P = .0031). The odds of providing consent is significantly higher for the patients whom a primary care physician has been involved in their medical care (OR = 1.323; P < .0001). Conclusion Individual-level characteristics are important predictors of patients' willingness to disclose their medical information on HIE platforms.